Structural insights into selectivity and cofactor binding in snake venom l-amino acid oxidases - Ullah, A. [UNESP]; Souza, T. A C B; Abrego, J. R B [UNESP]; Betzel, C.; Murakami, M. T.; Arni, R. K. [UNESP] (Elsevier, 2012)
l-Amino acid oxidases (LAAOs) are flavoenzymes that catalytically deaminate l-amino acids to corresponding α-keto acids with the concomitant production of ammonia (NH 3) and hydrogen peroxide (H 2O 2). Particularly, snake venom LAAOs have been attracted much attention due to their diverse clinical and biological effects, interfering on human coagulation factors and being cytotoxic against some pathogenic bacteria and Leishmania ssp. In this work, a new LAAO from Bothrops jararacussu venom (BjsuLAAO) was purified, functionally characterized and its structure determined by X-ray crystallography at 3.1å resolution. BjsuLAAO showed high catalytic specificity for aromatic and aliphatic large side-chain amino acids. Comparative structural analysis with prokaryotic LAAOs, which exhibit low specificity, indicates the importance of the active-site volume in modulating enzyme selectivity. Surprisingly, the flavin adenine dinucleotide (FAD) cofactor was found in a different orientation canonically described for both prokaryotic and eukaryotic LAAOs. In this new conformational state, the adenosyl group is flipped towards the 62-71 loop, being stabilized by several hydrogen-bond interactions, which is equally stable to the classical binding mode. © 2012 Elsevier Inc.
Keywords: Amino acid specificity; Bothrops jararacussu; Crystal structure; FAD-binding mode; L-Amino acid oxidase; amino acid oxidase; snake venom; crystal structure; crystallization; enzyme active site; enzyme purification; enzyme specificity; enzyme structure; enzyme substrate; hydrogen bond; hydrophobicity; molecular interaction; nonhuman; priority journal; structure analysis; Amino Acid Sequence; Animals; Bothrops; Crotalid Venoms; Crystallography, X-Ray; Enzyme Stability; Hydrophobic and Hydrophilic Interactions; L-Amino Acid Oxidase; Molecular Sequence Data; Protein Structure, Secondary; Eukaryota; Prokaryota